Information Services of Bangkok Metropolitan Administration’s Discovery Learning Libraries: Roles and Potential in Driving the Sustainable Development Goals (SDGs) - Saenwa, Sumattra; Prapinpongsakorn, Sasipimol (Journal of Arts and Thai Studies, 2025)
Background and Objectives: The Sustainable Development Goals (SDGs) are a set of global development goals adopted by the United Nations member states. Thailand has integrated the SDGs and the concept of sustainable development into its 13th National Economic and Social Development Plan. As a public library under this vision, Discovery Learning Libraries, Bangkok Metropolitan Administration (BMA) is an organization that operates under the aforementioned vision. Providing information services that respond to the SDGs is a key approach to modernizing libraries, aligning them with global contexts, and serves as a part of driving society toward sustainability. Therefore, the objective of this research is to study the information services and the role of Discovery Learning Libraries, BMA in driving the SDGs. Methods: This research used a qualitative research approach. The key informants were divided into two groups: 38 library personnel and 102 library users within the scope of the 34 Discovery Learning Libraries, BMA. The data were collected through semi-structured interviews and analyzed using content analysis. The research findings were presented in the form of dashboards, tables, and descriptive narration. Results: Discovery Learning Libraries, BMA play an important role in driving the SDGs across five essential dimensions, which clearly cover all 17 goals. However, challenges and gaps in driving the SDGs forward persist. For example, inter-organizational collaboration, which is consistent with its original mission, is not directly driven by the policies aimed at achieving the SDGs. A defined strategy plan and clear indicators are also lacking. Librarians are also unknowing of the SDGs, resulting in missed opportunities to improve existing services and activities with clearer goals. Instead of simply promoting reading or pursuing general goals, many initiatives are unable to measure and develop activities to their full potential for the SDG impact. Furthermore, there are limits due to a lack of materials and information resources that do not meet the needs of the users of every age group, which affects the creation and development of new activities. Personnel lack specialized skills and experience, as well as infrastructure and technology problems. Meanwhile, the needs of today’s users are becoming more particular and sophisticated. Users expect libraries to be places of opportunity for lifelong learning, career development, and quality of life enhancement. Recommendations for the library’s SDG implementation include developing and implementing a clear policy on the SDGs, developing and upgrading customized services, adapting management to a data-driven and flexible approach, and expanding collaborations based on its original mission to strategically seek partners to directly support the SDGs. Application of this study: Discovery Learning Libraries can utilize the findings to develop policy strategies and action plans that align with the SDGs and the BMA development plan. In practice, they can improve and develop libraries to better fulfill the needs of a wider variety of users and be as specific as possible to target groups by clearly linking them to each SDG goal as part of the SDGs' outreach to the public. Conclusions: This study reflects the current state and direction of learning libraries as public libraries when compared with the public library practices in other countries. To accomplish the SDGs by 2030, countries, including Thailand, need to work collaboratively to communicate, disseminate knowledge, and implement integrated activities as part of their responsibilities toward society. The impact and advantages will be assessed, resulting in changes in knowledge, skills, and behavior. The findings of this study can be utilized for both policy and practical purposes. At the policy level, they can inform strategic planning and action plans that align with the SDGs and the Bangkok Development Plan. At the practical level, the results can be applied to improve and develop the libraries to better meet the increasingly diverse and specific needs of target user groups, ensuring clear alignment with each relevant SDG goal.